Hydrogen refueling station cost model applied to five real case studies for fuel cell buses - Caponi Roberta (EDP Sciences, 2021)
Hydrogen Refueling Stations (HRS) are a key infrastructure to the successful deployment of hydrogen mobility. Their cost-effectiveness will represent an increasingly crucial issue considering the foreseen growth of vehicle fleets, from few captive fleets to large-scale penetration of hydrogen vehicles. In this context a detailed, component-oriented cost model is important to assess HRS costs for different design concepts, layout schemes and possible customizations, respect to aggregate tools which are mostly available in literature. In this work an improved version of a previously developed component-oriented, scale-sensitive HRS cost model is applied to 5 different European HRS developed within the 3Emotion project with different refueling capacities (kgH2/day), hydrogen supply schemes (in-situ production or delivery), storage volumes and pressures and operational strategies. The model output allows to assess the upfront investment cost (CAPEX), the annual operational cost (OPEX) and the Levelized Cost of Hydrogen (LCOH) at the dispenser and identify the most crucial cost components. The results for the five analyzed HRS sites show an LCOH at the nozzle of around 8-9 €/kg for delivery based HRSs, which are mainly dominated by the H2 retail price and transport service price and around 11-12 €/kg for on-site producing HRS, for which the electrolyzer CAPEX and electricity price plays a key role in the cost structure. The compression, storage, and dispensing sections account for between 1-3 €/kg according to the specific design & performance requirements of the HRS. The total LCOH values are comparable with literature, standard market prices for similar scale HRSs and with the 3Emotion project targets.